AKTIVITAS SOSIAL KEAGAMAAN SANTRI YAYASAN AMAL SALEH AIR TAWAR BARAT KOTA PADANG - Folandra, Danil (Potret Pemikiran, 2020)
This article is motivated by the enthusiasm of students from public tertiary institutions in religious activities. The lack of religious knowledge provided by the campus encourages them to deepen their religion by joining a religious institution. This type of research is a qualitative (field research). The data collection method uses observation, interviews, and documentation techniques. The data is then analyzed by means of data reduction, data display, and conclusion drawing. In this study, it was found that the institution of the Yayasan Amal Saleh Foundation was born to foster a young generation of Islam influenced by the emergence of Islamic reform movements both in Indonesia and the world. The organization has a program of activities which are categorized as religious activities and social activities which are motivated by religious motivation and social motivation. Members of the organization who call themselves â€œsantriâ€ assume that although they come from public tertiary institutions, they position themselves as religious people (Islam) so that they are embedded in themselves that these activities have become responsibilities that must be carried out. Also, as a social creature, the act of helping one another also becomes a necessity.Keywords: Yayasan Amal Saleh; Social Religion; Students; SantriArtikel ini dilatarbelakangi oleh semangat mahasiswa dari perguruan tinggi umum dalam kegiatan keagamaan. Minimnya ilmu agama yang diberikan oleh kampus menjadi pendorong mereka untuk lebih memperdalam agama dengan bergabung kepada sebuah lembaga keagamaan. Jenis penelitian ini ialah penelitian lapangan (field research) yang bersifat kualitatif. Metode pengumpulan data menggunakan teknik observasi, wawancara, dan dokumentasi. Data kemudian dianalisis dengan cara reduksi data, display data dan penarikan kesimpulan. Dalam studi ini ditemukan bahwa lembaga Yayasan Amal Saleh ini lahir dalam rangka membina generasi muda Islam yang dipengaruhi oleh munculnya gerakan pembaharuan Islam baik di Indonesia maupun dunia. Organisasi tersebut memiliki program kegiatan yang dikategorikan kepada kegiatan keagamaan dan kegiatan sosial yang didorong oleh motivasi agama dan motivasi sosial. Anggota organisasi yang menyebut dirinya sebagai santri ini beranggapan bahwa walaupun berasal dari perguruan tinggi umum tapi mereka memposisikan diri sebagai umat beragama (Islam) sehingga tertanam pada diri bahwa kegiatan tersebut sudah menjadi tanggung jawab yang harus diemban. Selain itu, sebagai makhluk sosial tindakan saling menolong juga menjadi suatu keharusan.Kata kunci: Yayasan Amal Saleh; Sosial Keagamaan; Mahasiswa; Santri